Determinants of Repeated Hospital Admission in Dialysis-Dependent Chronic Kidney Disease Patients : Repeated Hospital Admission in Dialysis-Dependent Chronic Kidney Disease Patients - Khan, Saqib; Khan, Muhammad Feroze; Azhar, Amer; Saeed, Sehrish (Pakistan Journal of Health Sciences, 2026)
Studies evaluating the factors leading to repeated hospital admissions in dialysis-dependent CKD patients are scarce in the context of local settings. Results of the study would benefit clinicians and patients in reducing hospitalization burden and health care costs by prompt management of potential factors leading to hospitalization. Objective: To determine the frequency of factors leading to repeated hospitalization in dialysis-dependent chronic kidney disease patients. Methods: The descriptive study was conducted at the Department of Nephrology, Khyber Teaching Hospital, Peshawar, during the period 11th May 2025 to 10th September 2025. A total of 176 male and female patients diagnosed with chronic kidney disease and receiving maintenance hemodialysis were enrolled. The patients were evaluated for factors leading to repeated hospitalization, including the presence of heart failure, anemia, mode of vascular access, and low serum albumin. Results: The mean age of patients was 58.68±6.73 years. 89 patients (50.6%) were female. Repeated hospitalization was recorded in 87 patients (49.0%). Factors of repeated hospitalization revealed heart failure in 82 patients (46.6%), anemia in 30 (17.0%), low albumin in 118 (67.0%), and AV fistula in 82 patients (46.6%) as a mode of vascular access. Female patients had more frequent repeated hospitalization (n = 45, 50.6%), p value 0.762. Conclusions: Heart failure, AV fistula usage, and low albumin were the most common variables associated with frequent hospitalization. A connection between hospitalization, duration, and cause of CKD was observed, but did not reach statistical significance.